Automatic Smart Light With Sound Detection and Fingerprinting Based on Arduino UNO - Fauziah (SEAN Institute, 2022)
Lights are one of the important components in lighting indoors and outdoors. Lights provide enormous benefits, especially at night. Light technology in providing lighting today has helped many people's activities in daily life. making other alternatives such as automatic smart lights that use modern technology so that the lights can turn on and off by utilizing an automatic light device by detecting Google's voice and Arduino Uno-based finger picking which can be received directly without having to touch the switch of the lamp. Because the lamp device is connected using a sound sensor which will be a parameter for the lamp and the Arduino UNO microcontroller as the brain of the process connected to the switch. The relay also functions so that the incoming electricity can be disconnected and connected automatically. If the input entered is read by the Arduino, the lamp can turn on based on the sound of finger picking and Google's voice. The purpose of this tool is to make it easier to turn off the lights, want to turn off the lights in a different way and save time without having to press the switch.